If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + -1x = 8x + 2 Reorder the terms: 2 + -1x = 2 + 8x Add '-2' to each side of the equation. 2 + -2 + -1x = 2 + -2 + 8x Combine like terms: 2 + -2 = 0 0 + -1x = 2 + -2 + 8x -1x = 2 + -2 + 8x Combine like terms: 2 + -2 = 0 -1x = 0 + 8x -1x = 8x Solving -1x = 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -1x + -8x = 8x + -8x Combine like terms: -1x + -8x = -9x -9x = 8x + -8x Combine like terms: 8x + -8x = 0 -9x = 0 Divide each side by '-9'. x = 0 Simplifying x = 0
| P=-0.002t^2+0.056t+0.889 | | -2(3k-8)=2(-k+2) | | Z=4x^2-9y^2-36 | | 64x^2-112+49=0 | | 3+[5-2(4+1)]= | | 2/3*3+2 | | X/52=14/13 | | 3x+4=3(x-8) | | 21/x=7/4 | | 4y=2/3y+10 | | 3y-9+y+43=7y+40-5y | | 6x-15=3x+27 | | y-8=-5/3(x+5) | | 3t^2-5=t^2+27 | | t^2-48t+68=0 | | 4x-20/3x-15 | | -8k^2=10 | | 6x-(2x+4)=5x-32 | | 0.08(y-2)+0.04y=0.02y-0.01(40) | | 3(1+x)=4+2x | | 4(x+2)=-6+4x | | y=1/3*-3 | | 28x^2+27x-81=0 | | 4(2w+5)=7(2w-4) | | 7x+24=3x-20 | | -7+3x=x-3 | | x+1=4x-8 | | 2x-2(-2x+4)=-68 | | (x-6)/(x-3) | | 3(2y-3)=81 | | 7/10-1/5 | | x/3+6=12 |